Pengaruh Citra Merek, Kepercayaan Merek, dan Keamanan Privasi Terhadap Keputusan Pengguna Gojek - Valentine Teja Wijaya; Bruno Hami Pahar (BIP's JURNAL BISNIS PERSPEKTIF, 2022)
Gojek is an Indonesian technology company engaged in services through motorcycle taxi services. Gojek itself has more than 20 services offered and is a solution to everyday challenges, ranging from transportation, food delivery, shopping, delivery of goods, payments, massages, to cleaning houses and vehicles. Researchers conducted research on Gojek application users in Surabaya. This research is a research with quantitative method. The sampling technique used is purposive sampling and uses questions on a questionnaire distributed to 75 respondents who are Gojek application users who are at least 17 years old and have used the Gojek application in Surabaya at least 2 times. Thisresearch was conducted using validity test, reliability test, descriptive test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression test, determinant coefficient, F test, and t test. The t-test in this study states that the brand image variable (X1) on purchasing decisions (Y) has a t-count value of 1.624 < t-table 1.993 with a significant level of 0.109 > 0.050 which means that brand image has no effect on purchasing decisions of Gojek application users, the trust variable brand (X2) on purchasing decisions (Y) has a t value of 3.209 > t table 1.993 with a significant level of 0.002 < 0.050 which means that brand trust affects the purchasing decisions of Gojek application users, and the privacy security variable (X3) on purchasing decisions (Y) has a t value of 4.018 > t table of 1.993 with a significant level of 0.000 < 0.050 which means that privacy security affects the purchasing decisions of Gojek application users. The results of this study conclude that brand trust and privacy security have a significant effect on the decisions of Gojek users in Surabaya, while brand image does not affect the decisions of Gojek users in Surabaya.